Finite element simulation of ultrasonic-assisted machining: a review - Lotfi, Mohammad; Akbari, Javad (International journal of advanced manufacturing technology, 2021)
Ultrasonic-assisted machining is an advanced method which could improve the process of machining. Besides, simulation modeling process is a method to help the researchers analyze different aspects of the process with more details in a shorter time. Simulation of ultrasonic-assisted machining is also a field of research that is of interest to researchers working in the field of machining processes. In recent years, a variety of papers have been published where cutting forces, chip formation, tool wear and temperature, and microstructure changes were simulated. That being the case, a review paper is required to represent the advances implemented by researchers in the simulation of ultrasonic-assisted machining process. Moreover, the difficulties and necessities of this process are mentioned at the end of this review paper.